2007
DOI: 10.1001/archpsyc.64.5.602
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Cost-Related Medication Nonadherence in Medicare Beneficiaries

Abstract: Context: Treatment for depression can be expensive and depression can affect the use of other medical services, yet there is little information on how depression affects the prevalence of cost-related medication nonadherence (CRN) in elderly patients and patients with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 35 publications
2
39
1
Order By: Relevance
“…This finding is broadly consistent with other Medicare studies, which find higher rates of nonadherence among adults with poor health, chronic disease, and disabilities. 18,20,23 These disparities may be explained by another factor not included in this analysisthe number of drugs prescribed. Simply put, a higher number of prescriptions presents more frequent opportunities for nonadherence, and patients with more serious chronic conditions or multiple chronic conditions are prescribed more medicines than are those without chronic conditions.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is broadly consistent with other Medicare studies, which find higher rates of nonadherence among adults with poor health, chronic disease, and disabilities. 18,20,23 These disparities may be explained by another factor not included in this analysisthe number of drugs prescribed. Simply put, a higher number of prescriptions presents more frequent opportunities for nonadherence, and patients with more serious chronic conditions or multiple chronic conditions are prescribed more medicines than are those without chronic conditions.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…[18][19][20] Other patient attributes positively associated with cost-related nonadherence are racial or ethnic minority status, 12,17 female gender, 18 lack of health insurance or prescription drug coverage, 9,16,17,21,22 low income, 18 and disability or chronic illness. 18,23 Yet, clinicians observe that patients with similar health conditions, sociodemographic attributes, and socioeconomic status may make very different choices when it comes to filling their prescriptions. 24 These differences in adherence are often attributed to the quality of the patient-provider interactions; [25][26][27] the salient nontherapeutic features of the drugs prescribed, including the complexity of regimens; 28,29 and the occurrence of unpleasant sideeffects or drug interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing drug costs and capping prescription benefits (Hsu et al 2006) have limited access to essential drugs, resulting in increased emergency department (ED) visits, hospitalizations, and long-term care admissions (Adams et al 2001;Cox et al 2001;Goldman et al 2007;Mojtabai and Olfson 2003;Rector and Venus 2004;Shih 1999;Tamblyn et al 2001;Tseng et al 2004). Although increased consumer cost-sharing has been shown to decrease prescription drug use and result in adverse health outcomes in chronic illnesses such as congestive heart failure (Cole et al 2006), lipid disorders (Gibson et al 2006a, b), diabetes (Mahoney 2005), depression (Bambauer et al 2007) and schizophrenia (Soumerai et al 1994), little is known about the influence of increased consumer cost-sharing on antiretroviral therapy use or clinical outcomes in HIV-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…A US internet survey found that more than 30% of active elderly reported CRN [31]. Disease itself and polypharmacy may increase the likelihood of engaging in non-adherence [32,33]. The costs of medication, prescription drug coverage, insurance coverage and income have all been reported as predictors of CRN [34,35].…”
Section: Introductionmentioning
confidence: 99%